(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The study included the isolation and diagnosis of the fungi from the Desktop’s of the tables (instructers ,medical laboratories). The study appeared many of the different kinds of fungi:(Absidia sp,Candidia sp, Aspergillus sp,Penicillum sp and Alternaria sp) The rate of appearance of the type of the fungi in Desktop’s of the tables instructers is the higher than the Desktop’s of the tables of the medical laboratories . The rate of appearance of the fungi Candidia is recoded 36.8% and Penicillum sp,Aspergillus niger is recoded 21.05% and Aspergillus flavus recoded 5.2 %, Abisidia sp recoded 15.7%. While in the Desktop’s of the tables medical laboratories the fungi Aspergillus terrus is recorded 15.7% and the fungi Absidia ,Candidia, Apergillus niger is recoded 20% , Penicillum sp ,Alternaria sp is recoded 10%. The study showed the influence of the hot water extract of the Nigella sative the concentration which is used(10,20,30, 40) mg /ml on some of fungi. The rate of reduction is appeared 100% of the fungi Penicillum sp in the concentration (30,40) mg/ml and the range of the diameter colony of the yeast Candidia albicanis in the concentration 30 mg/ml the (1)cm. While the fungi Aspergillus niger in the concentration (10,20)mg/ml is given resistance toward the extract 2.